Characterisation of the gastrointestinal mucosa‐associated microbiota: a novel technique to prevent cross‐contamination during endoscopic procedures. Issue 11 (18th April 2016) - Shanahan, E. R.; Zhong, L.; Talley, N. J.; Morrison, M.; Holtmann, G.
Summary: Background: The mucosa‐associated microbiota appears to be highly relevant to host–microbe interactions in the gastrointestinal (GI) tract. Thus, precise characterisation of the mucosa‐associated microbiota may provide important insights for diagnostic and therapeutic development. However, for technical reasons, mucosal biopsies taken during standard endoscopic procedures are potentially contaminated by GI luminal contents. Aim: To develop and validate a biopsy device that minimises contamination during sampling of the mucosa‐associated microbiota. Methods: A new, encased biopsy forceps was developed, the Brisbane Aseptic Biopsy Device (BABD). This comprises sterile forceps encased by a sheath with a plug at the tip, allowing targeted, aseptic sampling of the mucosa. Matched duodenal biopsies were obtained using the BABD, standard biopsy forceps, and a sterile brush, from patients undergoing upper GI endoscopy for iron deficiency ( n  = 6). Total genomic deoxyribonucleic acid (gDNA) was extracted from samples and bacterial 16S rRNA gene libraries sequenced to investigate the mucosa‐associated microbiota. Results: Microbial DNA was recovered from biopsies obtained by the BABD, confirming the presence of a duodenal mucosa‐associated microbiota. This microbiota was dominated by the genus Streptococcus, with lower levels of Prevotella, Veillonella and Neisseria . At the individual patient level, substantial differences were observed between matched samples obtained using the different devices. A greater degree of bacterial diversity was observed in samples collected using the standard forceps, indicating the BABD affords collection of samples more representative of the mucosa‐associated microbiota, by precluding luminal cross‐contamination. Conclusions: Cross‐contamination can occur when mucosal biopsies are taken during standard endoscopic procedures. Utilising the novel Brisbane Aseptic Biopsy Device can reduce cross‐contamination, and it offers improved opportunities to more precisely examine host–mucosa‐associated microbiota interactions.